Cross Clinical Reactivity among Wild Privet and Gaint Hazel Pollinosis (Asian Journal of Pharmaceutics (AJP), 2023)
Background: Pollen from various tree and grass species is the most common cause of allergy responses aroundthe world. Objectives: In this study, we focused on the allergenic potential and cross-reactivity between pollenextracts of Ligustrum robustum and Corylus maxima, aiming to understand the clinical significance of theseinteractions. Several proteins found in Ligustrum pollen have previously been identified as allergens thatcause sensitization and the onset of allergic symptoms in atopic people. Our study includes the cross-reactivitybetween pollen extracts of L. robustum with C. maxima for clinical significance. Methods: Immunological andbiochemical characterization was carried out for the purified GST compound which was assessed by sodiumdodecyl sulfate polyacrylamide gel electrophoresis. The cross-reactivity studies among allergens and relevantspecies were evaluated by enzyme-linked immunosorbent assay inhibition assays. Results: In biochemical assays,central goods and services tax (c-GST) was not enzymatically active, whereas l-GST demonstrated high enzymaticactivity. Conclusion: This research contributes to a better understanding of the allergenic properties and crossreactivitypatterns between these two pollen sources. The obtained information could have implications for thedevelopment of diagnostic and therapeutic strategies for individuals with allergies.